EFEKTIFITAS PENGATURAN QUICK OF BLOOD (QB) TERHADAP RASIO REDUKSI UREUM PLASMA PADA PASIEN CKD YANG MENJALANI HEMODIALISIS DI RST DR. SOEDJONO MAGELANG: THE EFFECTIVENESS OF ADMINISTRATION OF QUICK OF BLOOD (QB) ON THE RATIO OF UREUM PLASMA REDUCTION IN CKD PATIENTS TAKING HEMODIALYSIS IN RST DR. SOEDJONO MAGELANG - Endro Haksara; Ainnur Rahmanti (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
The main function of the kidneys under normal conditions is to regulate fluids and electrolytes and the acid-base composition of body fluids, remove metabolic wastes that are no longer needed by the body, regulate blood pressure and hormonal function. Chronic Kidney Disease (CKD) is the final stage of chronic kidney failure where GFR <15 ml/min/1.73m2 so that the body fails to maintain metabolism and fluid and electrolyte balance, causing uremia, namely retention of urea and other nitrogenous wastes in the blood (Smeltzer et al. al, 2008; National Kidney Foundation in Kallenbach, et al, 2005). With the increasingly real decline in kidney function or worsening of symptoms of uremia, renal replacement therapy is required for survival, namely dialysis and organ transplantation. There are two methods of dialysis, one of which is Hemodialysis (Potter, 2005; Smelzer, 2008). Cases of chronic kidney failure in the world have increased by more than 50%, in the United States which is a very developed country every year there are about 20 million adults suffering from chronic kidney failure and undergoing hemodialysis in more than 100,000 patients, while in Indonesia, according to the Indonesian Kidney Diatrans Foundation, YDGI), in 2007 there were about 100,000 chronic kidney failure patients but only a few patients were able to undergo hemodialysis. Kidney replacement therapy in Indonesia was started in 1972 in Jakarta (Dr. Cipto Mangunkusumo Hospital/FKUI), in Bandung in 1976 (Hasan Sadikin Hospital/FK UNPAD).